Spheroidal antennas with metamaterials coatings and phase mode processing for wireless communications - Huang, Ming Da (2010)
This thesis focuses on the theoretical study of electromagnetic scattering and radiation by a conducting spheroid with metamaterials (MTMs) coatings (Part I) and phase mode processing for spherical and spheroidal antenna arrays (Part II).